Depression in paediatric chronic fatigue syndrome. Issue 6 (25th April 2013) - Bould, Helen; Collin, Simon M; Lewis, Glyn; Rimes, Katharine; Crawley, Esther
Abstract : Objective: To describe the prevalence of depression in children with chronic fatigue syndrome (CFS)/myalgic encephalomyelitis (ME) and investigate the relationship between depression in CFS/ME and clinical symptoms such as fatigue, disability, pain and school attendance. Design: Cross-sectional survey data using the Hospital Anxiety and Depression Scale (HADS) collected at assessment. Setting: Specialist paediatric CFS/ME service in the South West. Patients: Children aged 12–18 years with CFS/ME. Main outcome measure: Depression was defined as scoring >9 on the HADS depression scale. Results: 542 subjects had complete data for the HADS and 29% (156/542) (95% CI 25% to 33%) had depression. In a univariable analysis, female sex, poorer school attendance, and higher levels of fatigue, disability, pain, and anxiety were associated with higher odds of depression. Age of child and duration of illness were not associated with depression. In a multivariable analysis, the factors most strongly associated with depression were disability, with higher scores on the physical function subscale of the 36 item Short Form (SF-36). Conclusions: Depression is commonly comorbid with CFS/ME, much more common than in the general population, and is associated with markers of disease severity. It is important to screen for, identify and treat depression in this population.